Development Of An Instrument To Measure Psychological Violence By Teachers - Tita Rosita (Jurnal Counseling Care, 2025)
AbstractPsychological violence committed by teachers has a negative impact on students' mental health. The purpose of this study is to create an instrument to measure psychological violence committed by teachers during classroom learning which includes aspects of indifference, humiliation, isolation, rejection, and terror. The research method used is quantitative descriptive research. The development of the questionnaire in this study incorporates a measurement framework that provides a systematic way based on a combination of theoretical and psychometric approaches. The sample was 146 students of one of the vocational schools in East Bandung Regency. Based on the results of the study, it was found that the teacher psychological violence questionnaire consisted of 18 question items covering five aspects, namely (1) indifference, (2) humiliation, (3) isolation, (4) rejection, and (5) terror. The 18 items in the questionnaire have met the standards of reliability, content validity, construct validity, and provide preliminary evidence for the use of instruments with the aim of measuring psychological violence committed by teachers during classroom learning.Keywords : Psychological Violence; Teacher; Instrument.